"A bridge over troubled gaps": up-conversion driven photocatalysis for hydrogen generation and pollutant degradation by near-infrared excitation. Issue 15 (2nd February 2018) - Acosta-Mora, P.; Domen, K.; Hisatomi, T.; Lyu, H.; Méndez-Ramos, J.; Ruiz-Morales, J. C.; Khaidukov, N. M.
Abstract : We present evidence of NIR-to-UV-VIS photon conversion for degradation of organic dyes and hydrogen and oxygen evolution. Abstract : Spectral up-conversion (UC) has been attracting growing interest for the effective harvesting of the near-infrared (NIR) part of sunlight for photocatalytic hydrogen production and environmental purification. We present evidence of NIR-to-UV-VIS photon conversion for degradation of organic dyes and hydrogen and oxygen evolution via water-splitting by TiO2 and Rh–Cr oxide-loaded SrTiO3 :Al photocatalysts, respectively.